Spurious thrombocytopenia in the mother and baby – A red herring clinical entity (Indian Journal of Case Reports, 2022)
Spurious thrombocytopenia or pseudothrombocytopenia (PTCP) is an important clinical entity, in which the presence of autoantibodies or anticoagulants used during blood sampling causes in vitro clumping of platelet and thereby resulting in a falsely low automated platelet count. The most common cause of platelet clumping is ethylenediaminetetraacetic acid used as an anticoagulant in the blood samples. The other reasons for PTCP include the presence of autoantibodies such as cold agglutinin, giant platelet, and platelet satellitism. There are very few cases of spurious thrombocytopenia in the newborn period published in the literature. We are reporting a case of PTCP due to platelet satellitism in a baby born to a mother with a similar condition.